Sales Management System with Rapid Application Development and PIECES Approach - Al-Qadr, Nola Ardelia; Novita, Rice; Ahsyar, Tengku Khairil; Zarnelly, Zarnelly (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
In this era of rapid technological advancement, the computer business plays a crucial role in providing goods and services to meet societal needs. However, Andalas Computer, despite offering a diverse range of products and services, faces challenges in its sales process and stock management, which still rely on manual methods. This study aims to develop a sales management system to facilitate the company's sales. By employing the Rapid Application Development (RAD) method, system requirements analysis can be addressed with feedback from users. This research utilizes PIECES analysis to identify opportunities from various aspects. The study results in a sales management system tailored to user needs. System testing was conducted using blackbox testing, followed by user acceptance testing to gauge user reception of the system. The results of the testing showed a positive acceptance rate of 90%.